Additive manufacturing of polylactic acid scaffolds dip-coated with polycaprolactone for bone tissue engineering - Costabeber, Gabriel [UNESP] (2024)
Bone tissue engineering aims to create scaffolds that support bone regeneration, addressing the needs of approximately 1.71 billion people with bone structure problems worldwide. This study explores the fabrication and characterization of 3D-printed polylactic acid (PLA) scaffolds dip-coated with polycaprolactone (PCL), producing complex geometries with interconnected pores, specifically RoundBar Sphere and RoundBar Cube. The scaffolds were then coated with PCL solutions of 0.5 % and 1 % concentrations, applying up to three layers. Surface topology analysis indicated that PCL coating slightly reduced pore size (1150 µm to 900) while improving coverage and integrity. After coating, Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of PCL on scaffold surfaces (characteristic bands at 1726, 1175 and 728 cm−1), whose a better coverage was obtained with more layers and higher concentrations of PCL. Coated scaffolds showed not significant change in compressive strengths (2–12 MPa), remaining suitable for trabecular bone applications. Hemolysis assays of the 3D scaffolds promoted non-hemolytic properties (0 % hemolysis), ensuring their blood compatibility. Metabolic activity (>70 %) and live/dead cell assays in human dermal fibroblasts (HDF) exhibited biocompatibilities for all samples, with coated scaffolds promoting enhanced cell proliferation compared to uncoated ones. Additionally, osteoblast metabolic activity (>90 %) and osteoblasts scratch assay demonstrated coated scaffolds promoted an area reduction of 1.36 and 1.53-fold higher than the control group and uncoated scaffold, respectively. In short, these coated scaffolds are promising candidates for bone tissue engineering and bone repair applications.